2001
DOI: 10.1007/s002280100331
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of tacrolimus in adult recipients receiving living-donor liver transplantation

Abstract: Nonlinear mixed-effect modeling was useful for analysis of pharmacokinetic characteristics of tacrolimus in LDLT patients. Immediately after surgery, patients receiving LDLT showed a smaller CL value than other transplant patients, and CL value increased with POD within 30 days after surgery. The estimated population pharmacokinetic parameters can be applied for a priori dosage calculations in adult patients with LDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In addition, the apparent clearance of tacrolimus at 3 weeks after LDLT was approximately twice that at 1 week ( Table 2). We previously reported that the total-body clearance of tacrolimus in LDLT patients was increased according to the POD because of the regeneration of grafted liver [8,9]. According to the previously estimated population pharmacokinetic parameters [8], a typical adult LDLT recipient in this study (grafted liver weight of 611 g, normal hepatic and renal function, and body weight of 67.1 kg during week 1 and 63.5 kg during week 3)…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition, the apparent clearance of tacrolimus at 3 weeks after LDLT was approximately twice that at 1 week ( Table 2). We previously reported that the total-body clearance of tacrolimus in LDLT patients was increased according to the POD because of the regeneration of grafted liver [8,9]. According to the previously estimated population pharmacokinetic parameters [8], a typical adult LDLT recipient in this study (grafted liver weight of 611 g, normal hepatic and renal function, and body weight of 67.1 kg during week 1 and 63.5 kg during week 3)…”
Section: Discussionmentioning
confidence: 63%
“…Levy et al [7] reported that a new monitoring strategy based on C 2 levels was superior to traditional C 0 monitoring for liver transplant recipients in reduction of the incidence and severity of acute rejections. Therefore, the relationship between C 0 and AUC of tacrolimus should be clarified in adult LDLT patients, because the pharmacokinetics of tacrolimus during the early post-transplantation period may fluctuate widely, according to the regeneration of grafted liver [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been hypothesised that high serum creatinine may be a surrogate indicator of a subclinical hepatic injury that causes altered renal blood flow 15 or some other alteration in drug metabolism related to the hepatorenal syndrome. 16 It is also possible that the impact of creatinine clearance in our model could be driven by changes in bioavailability caused by renal dysfunction. Notably, a study in rats found increased tacrolimus bioavailability in those animals with cisplatin-induced renal failure versus animals with normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Day posttransplant was a significant covariate towards tacrolimus where TVCl/F is 33% higher in the first nine days posttransplant compared to after day 9 which is consistent with other studies. ( 14 , 23 , 70 , 71 , 82 , 83 ) The higher TVCl/F may be due to early physiological changes such as fluid status, hepatic and kidney function and/or decreased bioavailability from dietary changes or concomitant medications. Concomitant steroid use was associated with a 23% higher tacrolimus TVCl/F most likely because steroids induce CYP3A enzymes.…”
Section: Discussionmentioning
confidence: 99%